COMPARATIVE PHARMACOGNOSTIC STUDIES OF ROOTS OF ASHWAGANDHA (WILD, NAGORI AND POSHITHA VAR) - Akshatha.M; Giri Prashanth K.G; Shiva Manjunath M.P; Seema Pradeep (AYUSHDHARA, 2018)
Background: Ashwagandha is a very well-known herb in Ayurveda. It is widely used in pharmaceutical, cosmetic, agricultural, food industries, and is a constituent of over 200 Ayurvedic formulations. The annual demand of Ashwagandha is 7000 tons but its actual availability is just 1500 tons, this demand is not met by using the wildly grown Ashwagandha. To meet this demand, it has been brought under cultivation many centuries ago, in India. Numerous cultivated varieties of Ashwagandha are developed for high yield and better quality roots. Amongst them, Nagori Ashwagandha is a popular variety, cultivated for its demand. Poshitha Ashwagandha is a high yielding and improved variety released by CSIR-CIMAPS. The current study aims at comparing the roots of wildly grown Ashwagandha, Nagori Ashwagandha and Poshitha Ashwagandha, pharmacognostically. Methodology: The study deals with macroscopic parameters, microscopic study of transverse sections physicochemical, phytochemical analysis and powder microscopy of roots of the three varieties of Ashwagandha. Results: Significant macroscopic differences were noted between the wild and the two cultivated varieties of Ashwagandha roots, there was no much variation in the physico-chemical and phyto-chemical parameters amongst the three, also there was no much difference found between the two cultivated varieties- morphologically and phyto-chemically.